The gift of touch : embodying the good - Ross, Stephen David (State University of New York Press, 1998)
Traces Western ideas of corporeal bodies from Plato to contemporary feminist and postructuralist writings, with the purpose of reexamining the good, identified in Plato as that which gives authority to knowledge and truth. -- Provided by publisher.